“After the floods, he says he is an environmentalist”: Understanding blended roles and organizational boundaries in decision-making under uncertainty during unprecedented floods in Wayanad, India - Koshy, Mrudhula (Frontiers in Sustainable Cities, 2022)
An increase in unprecedented environmental crises as a result of climate change and human influence has amplified calls for recognizing the complexity of decision-making under uncertainty (DMUU). The microdynamics of how decision-makers act in institutional settings under uncertainty has however received limited attention in decision-making in planning practice. This article investigates DMUU in the context of Wayanad, a peri urban hill district in Kerala, India through two decision settings; the unprecedented heavy monsoon floods in 2018 and 2019 as a case of short-term uncertainty, and quarrying in ecologically sensitive areas as a case of long-term uncertainty. Through empirical findings from semi-structured interviews of 58 decision-makers from state and non-state actors, group discussions, and participatory and non-participatory observations, the article discusses the aspects of individual and collective actions made before, during and after the floods by combining insights from spatial planning and governance literature underpinned by political ecology narratives. The article discusses barriers to decision-making under short- and long-term uncertainty in Wayanad, and the spatial-temporal dimensions linking individual and collective actions. It argues that factors such as community resourcefulness and decentralized governance appeared to facilitate effective decision-making under short-term uncertainty but did not contribute intrinsically to decision-making under long-term uncertainty. The article concludes with recommendations for potential improvements in decision-making under long-term uncertainty in contexts with weak institutional mechanisms, chronic vulnerabilities and resource scarcity, through structural organizational change, and decision-making frameworks that foregrounds heuristic, flexible, incremental, and cumulative actions across scales over time.